Identifikasi Dan Strategi Pengembangan UMKM Di Kecamatan Bengalon Kabupaten Kutai Timur - Prapdopo Prapdopo; Aris Satriyo Nugroho Nugroho; Donny Armandho Putra (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2021)
The policy of developing MSMEs and small industries has long been a concern of the Indonesian government. Various problems in empowering MSMEs are the low capacity of human resources, limited control and ownership of production assets, especially capital, concentration of work resources that are engaged in hereditary businesses, and low mastery of production process technology and marketing information. This study aims to identify MSMEs and formulate strategies for empowering MSMEs in Bengalon District in East Kutai Regency. Data collection techniques were carried out by, among others, using the method Rapid District Appraisal (RDA) that included a literature study (documentation) in the form of a Bengalon sub-district profile, village profiles in East Kutai Regency in recent years, field studies and observations/surveys/observations. A participatory approach to obtain data/information and assessment general in the field. The results showed that 1) Administrative and Institutional Aspects, there are 6 (six) MSMEs that fall into the important and urgent categories; 2 (two) MSMEs that are categorized as not important but urgent and 2 (two) MSMEs that are facing important but not urgent institutional problems; 2) Aspects of Production, there are 7 (seven) MSMEs that fall into the important and urgent category and 3 (three) MSMEs that face important but not urgent institutional problems; 3) Aspects of the Scope of Marketing, there are 2 (two) MSMEs that fall into the important and urgent category and 8 (eight) MSMEs that face important but not urgent marketing problems; 4) Aspect of Capital, there are 2 (two) MSMEs which are categorized as important and urgent and 6 (six) MSMEs that face important but not urgent capital problems, and 2 (two) MSMEs which are categorized as urgent but not important; 5) Aspects of Assistance, there are 2 (two) MSMEs that fall into the important and urgent category and 6 (six) MSMEs that need important but not urgent assistance, and 2 (two) MSMEs that fall into the urgent but not important category; and 6) Promotion Aspect, there is 1 (one) MSME which is categorized as important and urgent and 9 (nine) MSME which is categorized as important but not urgent.